ISOLATION AND STRUCTURE ELUCIDATION OF THE CUSHION PLANT POTENTILLA ARTICULATA - Muhammad Hanafi; Shibata Kozo; Mamoru Kanzaki (Jurnal Kimia Terapan Indonesia, 1996)
Methanol extract of the whole plant of P. articulata Franch was fractionated by using open column silica gel chromatography following identification, resulted in the isolation of known phytoceramides, N-(2'-hydroxy-acyl)-2-amino1,3,4trihydroxy-8-octadecene) (1), which also isolated from Urtioca dioca and Thylacospermum caespitosum, and two known steroids, identified as ~-sitosterol (2), 3B-O-B-D-glucopyranosylsitosterol (3), which have also been isolated from Prunella vulgaris L. var. Iilacina (Labiatae). Triterpenoic acids were elucidated as 2B,19a-dihydroxyursolic acid (4), a mixture of Zcc-monohydroxyursclic acid (5) and 2a-monohydroxyoleanolic acid (6), also found in Geurn japonicum Thunberg, 19a-monohydro-xyursolic acid (7), a mixture ursolic acid (8) and oleanolic acid (9), which were also obtained in Isodon japonicus Hara. Their structure identifi-cations were based on chemical and spectroscopic methods.